2017
DOI: 10.1007/s11255-017-1670-3
|View full text |Cite
|
Sign up to set email alerts
|

3-T multiparametric MRI characteristics of prostate cancer patients suspicious for biochemical recurrence after primary focal cryosurgery (hemiablation)

Abstract: Post-PFC mpMRI, at Phoenix suspicion of BCR, may help identify a significant number of patients failing post-PFC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…Thus, disappearance of an MRI-visible lesion was associated with the treatment, but did not specifically indicate eradication of cancer. In a retrospective study with limited biopsy correlations, Kongyuy et al reported a similar observation 28 . The role of MRI in evaluating response to treatment remains a subject for further investigation.…”
Section: Commentmentioning
confidence: 65%
“…Thus, disappearance of an MRI-visible lesion was associated with the treatment, but did not specifically indicate eradication of cancer. In a retrospective study with limited biopsy correlations, Kongyuy et al reported a similar observation 28 . The role of MRI in evaluating response to treatment remains a subject for further investigation.…”
Section: Commentmentioning
confidence: 65%
“…PSA level among these studies ranged from 0.02 to 123, with a mean value from 5.9 to 12.24 ng/mL. Only 4 studies reported the data of prostate volume, in spite of the fact that some studies suggested it is possible to play a part in the diagnosis 17,18,21,32. Five studies performed the MRI with 1.5T scanners17,18,21,23,28 and the remaining 13 studies used 3.0T scanners 2,4,10,19,20,22,24,25,27,2932.…”
Section: Resultsmentioning
confidence: 99%
“…Only 4 studies reported the data of prostate volume, in spite of the fact that some studies suggested it is possible to play a part in the diagnosis 17,18,21,32. Five studies performed the MRI with 1.5T scanners17,18,21,23,28 and the remaining 13 studies used 3.0T scanners 2,4,10,19,20,22,24,25,27,2932. Except 5 studies,2,23,24,27,29,31 all of the others were used at least one type of endorectal, pelvic phased array (PPA), or body coil; moreover, 2 studies used two types of them (endorectal coil and PPA) 28,30.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations